Annual changes in the physical characteristics of Japanese Division I Collegiate American football players - Yamashita, D.; Kinoshita, S.; Sakaguchi, T. (International Journal of Strength and Conditioning, 2023)
We aimed to examine the annual changes in various physical characteristics of Japanese Division I (D1) Collegiate American footballers according to their positional groups. We measured body mass, and assessed performance in three gym tests (bench press, back squat, and power clean) and three field tests (40-yard dash, pro-agility shuttle, and broad jump) at each pre-season from 2014 to 2016 for players from a Japanese D1 university. Data from 55 players who completed = 50% (three out of six) of the performance measurements in consecutive years were used in this analysis. Performance data across the two positional groups (skill players and linemen) were analyzed using pairwise t-tests to determine annual changes. The skill players` body mass increased from their freshman to sophomore years (p < 0.05, Cohen`s d > 0.8), but not from their sophomore to junior or junior to senior years. The skill players` 40-yard sprint time was shorter between all the annual comparisons (p < 0.05, d > 0.8). The linemen`s body mass increased from their freshman to sophomore years, and maintained from their sophomore to junior years and junior to senior years. There were significant improvements in strength and power outputs, but limited improvements in the pro-agility run and broad jump among most of the annual class comparisons for each positional group. These results indicate that annual improvements in the physical characteristics occur nonlinearly for Japanese D1 footballers. They will benefit from targeted strength and conditioning programs. However, the improvements of jumping and agility performances may be limited.